Challenging the racialization of child sexual exploitation: Muslim men, racism and belonging in Rotherham - Britton, Joanne (Ethnic and racial studies, 2019)
This paper presents findings from original research exploring the impact on Muslim men of a child sexual exploitation scandal that attracted significant attention to the northern English town where they live and contributed to a sustained detrimental effect on local community relations. It foregrounds men's accounts to reveal their agency and resilience in responding to racism that they identified as resulting from the scandal. It reveals how their accounts disrupt dominant discourses foregrounding Muslim self-segregation and lack of integration, demonstrating positive attachments and claims to localized space, and commitment to belonging. In doing so, it shows how men's responses to racism challenge racialized forms of knowledge about Muslims. The paper draws attention to the significance of localized forms of belonging in facilitating the inclusion of Muslim minorities. It also highlights the importance of centring Muslim men as historically speaking subjects in accounts of issues involving them.